Embedded courts: judicial decision-making in China - Ng, Kwai Hang (Cambridge University Press, 2017)
"Judicial decision-making in China is laden with tension. Chinese courts are organized as a singular and unified system yet grassroots courts in urban and rural regions differ greatly in the way they use the law and are as diverse as the populations they serve. Based on extensive fieldwork and in-depth interviews, this book offers a penetrating discussion of the operation of Chinese courts. It explains how Chinese judges rule and how the law is not the only script they follow - political, administrative, social and economic factors all influence verdicts. This landmark work will revise our understanding of the role of law in China - one that cannot be easily understood through the standard lens of judicial independence and separation of powers. Ng and He make clear the struggle facing frontline judges as they bridge the gap between a rule-based application of law and an instrumentalist view that prioritizes stability maintenance"--